Post-consultation illness trajectories in children with acute cough and respiratory tract infection: prospective cohort study. (20th April 2018) - Wensaas, Knut-Arne; Heron, Jon; Redmond, Niamh; Turnbull, Sophie; Christensen, Hannah; Thornton, Hannah; Peters, Tim J; Blair, Peter S; Hay, Alastair D
Abstract: Background: Little is known about respiratory tract infection (RTI) severity in children following consultation. Objectives: To investigate post-consultation symptom trajectories in children with acute cough and RTI and whether baseline characteristics predict trajectory group. Methods: Prospective cohort study of 2296 children (3 months–16 years) whose parents were invited to report cough severity and duration using a 7-point Likert scale. Longitudinal latent class analysis (LLCA) was used to identify post-consultation symptom trajectories in the first 15 days, and multinomial models to predict class membership. Results: Complete data were available for 1408 children (61%). The best LLCA model identified five post-consultation symptom trajectory groups: 'very rapid recovery' (28.5%), 'rapid recovery' (37.7%), 'intermediate recovery' (18.2%), 'persistent symptoms' (9.5%) and 'initial deterioration with persistent symptoms' (6.0%). Compared with very rapid recovery, parent-reported severe cough in the 24 hours prior to consultation increased the likelihood of rapid recovery (OR 1.79 [95% CI 1.23, 2.60]), intermediate recovery (OR 2.13 [1.38, 3.30] and initial deterioration with persistent symptoms (OR 2.29 [1.26, 4.16]). Initial deterioration was also associated with 'severe barking cough' (OR 3.64 [1.50, 8.82]), 'severely reduced energy in the 24 hours prior to consultation' (OR 3.80 [1.62, 8.87] and higher parent-assessed illness severity at consultation (OR 2.21 [1.17, 4.18]). Conclusion: We identified five distinct symptom trajectory groups showing the majority of children improved post-consultation, with only one group experiencing illness deterioration. The few characteristics associated with group membership did not fall into a pattern that seemed clinically useful.